Distributional Implications of Government Guarantees in Mortgage Markets - Gete, Pedro; Zecchetto, Franco (Review of Financial Studies, 2018)
We analyze the removal of the credit-risk guarantees provided by the government-sponsored enterprises (GSEs) in a model with agents heterogeneous in income and house price risk. We find that wealth inequality increases, driven by higher mortgage spreads and housing rents. Housing holdings become more concentrated. Foreclosures fall. The removal benefits high-income households, while hurting low- and mid-income households (renters and highly leveraged mortgagors with conforming loans). GSE reform requires compensating transfers, sufficiently high elasticity of rental supply, or linking GSE reform with the elimination of the mortgage interest deduction. Received March 11, 2016; editorial decision May 5, 2017 by Editor Stijn Van Nieuwerburgh.